ASSESSING MINING PRODUCTIVITY IN KAZAKHSTAN: INDUSTRY AND FIRM-LEVEL ANALYSIS - Azhibay, Seribolat (Nazarbayev University School of Mining and Geosciences, 2022)
Productivity plays an essential role in the mining industry: its improvement is significant for domestic producers' long-term economic growth and competitiveness in the world market. Starting from the late nineteenth century, productivity has been increasing due to accessibility of high-grade ores, development in technology, innovations, improvement of the quality of healthcare, and workers’ education. However, in recent years, productivity has been decreasing worldwide. The main reasons cited for this decline are resource depletion, increasing costs for extracting lower quality and less accessible reserves, and reduced efficiency of existing, outdated technology and techniques. Understanding various factors affecting productivity can lead to better counteracting of these effects. Thus, mining productivity and factors that impact it need to be studied. This study investigates labor productivity in Kazakhstan’s mining industry from 2001 to 2020 with the main focus on energy consumption, expenditures on labor, capital, also on growth rates of production, employment, investment, and wages. In addition, it analyzes the relationship between productivity and key factors: capital per worker, energy intensity, recovery rate, head grade, waste ratio, and copper share, in the local firm KazMinerals. The results of statistical analysis for industry-level and regression analysis for the firm-level data indicate that regional industrial labor productivity has increased over the past twenty years by more than 5% on average. Furthermore, the research shows a high correlation between productivity and ore grade, recovery rate, energy consumption, and capital per worker.
Keywords: Type of access: Open Access; mining productivity; firm-level analysis; mining industry; waste ratio; KazMinerals